Exclusive breastfeeding determinants among healthcare professionals in Northern Ghanaian hospitals: a cross-sectional study - Tina Wepeamo Wepeba; Robert Kokou Dowou; Miriam Linda Akeriwe; Winifred P. Wondong; Abdulai Abubakari; Gifty Apiung Aninanya (Journal of Health, Population and Nutrition)
Abstract Exclusive breastfeeding (EBF) can significantly reduce infant morbidity and mortality. However, evidence suggests that most health professionals fail to practice EBF. This research assessed factors that affect the practice of EBF among 320 randomly selected nursing mothers who are nurses and midwives in major hospitals. A cross-sectional study in four public hospitals in Tamale Metropolis, Ghana, involved 320 female nurses and midwives. Data was collected through a pretested questionnaire, and STATA version 17 was used for statistical analysis. Predictors of EBF were discovered using binary logistic regression models with statistical significance set at p < 0.05. A slight majority (53.1%) of the nurses and midwives reported practising EBF. Notably, over half (52.5%) of the participants demonstrated poor knowledge regarding EBF, despite a strong positive attitude towards it (81.6%). In conclusion, while the attitude towards EBF is generally positive among participants, there are significant gaps in knowledge. Determinants of the practice of EBF were income, living arrangement, parity, child’s age, complications after delivery, and knowledge level. The Ghana Health Service should mandate enhanced EBF training for nurses and midwives and this training should cover practical skills, address knowledge gaps, and be regularly updated and continuous professional development credits could be tied to successful completion.